Critical infrastructure risk in NHS England: predicting the impact of building portfolio age - Mills, Grant R. W.; Deka, Lipika; Price, Andrew D. F.; Rich-Mahadkar, Sameedha; Pantzartzis, Efthimia; Sellars, Peter (International Journal of Strategic Property Management, 2015)
NHS Trusts in England must adopt appropriate levels of continued investment in routine and backlog maintenance if they are to ensure critical backlog does not accumulate. This paper presents the current state of critical backlog maintenance within the National Health Service (NHS) in England through the statistical analyses of 115 Acute NHS Trusts. It aims to find empirical support for a causal relationship between building portfolio age and year-on-year increases in critical backlog. It makes recommendations for the use of building portfolio age in strategic asset management. The current trend across this sample of NHS Trusts may be typical of the whole NHS built asset portfolio and suggests that most Trusts need to invest between 0.5 and 1.5 per cent of income (depending upon current critical backlog levels and Trust age profile) to simply maintain critical backlog levels. More robust analytics for building age, condition and risk-adjusted backlog maintenance are required. First Publish Online: 19 Jun 2015